Cone penetration testing in geotechnical practice - Lunne, Tom (Blackie Academic & Professional, 1997)
Penetration testing is one of the key methods of obtaining information on soil properties. The cone penetration test and its variant, the piezocone test, are the most common penetration tests performed throughout the world. This text discusses such testing.